Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of empathetic virtual characters on presence in narrative-centered learning environments

Abstract: Recent years have seen a growing interest in the role that narrative can play in learning. With the emergence of narrative-centered learning environments that engage students by drawing them into rich interactions with compelling characters, we have begun to see the significant potential offered by immersive story-based learning experiences. In this paper we describe two studies that investigate the impact of empathetic characters on student perceptions of presence. A study was initially conducted with middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…For additional functionality, the agent could also respond and interact adaptively through cognitive, emotional and motivational models of the user (e.g. Swartout et al 2006;Gratch et al 2007;Arellano et al 2008;McQuiggan et al 2008), or interact with natural language, all of which can add to its believability. The advantages of accessibility in real time and customization are significant, but not if considerable time is required to construct these personalized agent social models.…”
Section: Anthropomorphic Virtual Agents Implemented As Social Modelsmentioning
confidence: 99%
“…For additional functionality, the agent could also respond and interact adaptively through cognitive, emotional and motivational models of the user (e.g. Swartout et al 2006;Gratch et al 2007;Arellano et al 2008;McQuiggan et al 2008), or interact with natural language, all of which can add to its believability. The advantages of accessibility in real time and customization are significant, but not if considerable time is required to construct these personalized agent social models.…”
Section: Anthropomorphic Virtual Agents Implemented As Social Modelsmentioning
confidence: 99%
“…A compelling argument for presence being fundamentally tied to agency and environment control has been made [16]. Further, there is support that narrative based virtual environments have an impact on increased presence [24].…”
Section: Virtual Experience Testmentioning
confidence: 99%
“…One area of research has focused on developing lifelike virtual characters or animated pedagogical agents (APA) for ITS, offering the possibility of engaging and motivating students within a learning task through verbal and nonverbal communication [1,2]. Previous research has demonstrated that a virtual agent's level of embodiment plays a significant role.…”
Section: Introductionmentioning
confidence: 99%